Two-photon Imaging of the Immune System - Dzhagalov, Ivan L (2012)
Two-photon microscopy is a powerful method for visualizing biological processes as they occur in their native environment in real time. The immune system uniquely benefits from this technology as most of its constituent cells are highly motile and interact extensively with each other and with the environment. Two-photon microscopy has provided many novel insights into the dynamics of the development and function of the immune system that could not have been deduced by other methods and has become an indispensible tool in the arsenal of immunologists. In this unit, we provide several protocols for preparation of various organs for imaging by two-photon microscopy that are intended to introduce the new user to some basic aspects of this method.